Types and forms of the enterprise’s self-sufficiency demonstration - М.I. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article investigates the essence of the concepts of types and forms of self-sufficient development of enterprises, proposes their main characteristics and conditions of economic activity. It is established that today, most forest enterprises show a very low efficiency level in terms of profits, investment, labour costs and rising business values. It is expedient to carry out species differentiation of self-sufficiency of the enterprise according to time signs of estimation. In the managerial sense, it allows us to distinguish retrospective, budgetary, current and strategic self-sufficiency, which characterize the economic development in the past, what it should be, what it is now and will be in the future. Depending on the manifestation of types of self-sufficiency, it is divided into the following forms: implemented; normally stable; exemplary; dynamic; prognostic. The form of representation of the level of self-sufficiency should be understood as a manifestation of its specific content, which is an object characterized by a system of indicators that serve as an analytical basis for making appropriate management decisions. Resources that meet the consumer needs of the technological process of economic activity are essential for ensuring self-sufficiency. To do this, it is necessary to determine the status of resources from the standpoint of their participation in the process of obtaining values and added value, expanded innovation and growth of the market value of the enterprise. The efficiency of resource participation in ensuring self-sufficiency of enterprises involves achieving their full employment and full management on the basis of the most necessary activities in assessing the formation of the maximum ratio between net income and the cost of obtaining it.